Nghiên cứu tổng hợp biodiezel từ dầu đậu nành trên xúc tác NaOH/MgO - Thanh và cộng sự, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
There is an increasing interest in many countries to research suitable alternative fuels that are environmental friendly. Biodiesel is one of them. Biodiesel has been synthesized on MgO catalyst activated by NaOH. This catalyst system is prepared by loading NaOH on MgO in an identified ratio. After finding out the best catalyst sample, some parameters such as reaction time, reaction temperature etc. have been studied for optimizing the reaction.